THE INFLUENCE OF THE INGOT MOLD COOLING ON THE STRUCTURE OF SILUMINA CASTINGS AK15M3 AT VERTICAL CENTRIFUGAL CASTING - V. Yu. Stecenko; K. N. Baranov; R. V. Konovalov (Литьë и металлургия)
Influence of ways of the mold cooling on structure of castings with diameter of 135 mm from AK15M3 silumin at vertical centrifugal casting is investigated. It is established that for production of castings with diameter 135 mm from AK15M3 silumin with high mechanical and tribotechnical properties it is necessary to apply a shaped mould with water-spray cooling at expense of cooler of 0,42 m3/h.